Biomonitorated study of Euphorbia umbellata (Pax) Bruyns extracts to be used to prepare silver nanoparticles with antimicrobial and cytotoxic potential (Research, Society and Development, 2022)
This study proposes to develop a biomonitorated study of the Euphorbia umbellata leaves extracts to identify those that could be used to prepare, by green synthesis, silver nanoparticles (AgNPs), with cytotoxic and antimicrobial potential. Hexane, dichloromethane, acetone, methanol, and aqueous extracts were evaluated to measure the terpenes amounts, antimicrobial activity (Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus), and the cytotoxic potential (A549, H292 cell lines). Characterization of AgNPs was performed by determination of zeta potential, polydispersity index, mean diameter, UV/Vis spectrometry, and scanning electron microscope (SEM), and evaluated against cytotoxic and antimicrobial models. Hexane and dichloromethane extracts presented the higher amounts of terpenes, exhibited microbiological inhibition against K. pneumoniae and S. aureus, and cytotoxic potential against both cell lines. AgNPs prepared with hexane and dichloromethane extracts were determined after 35 minutes of artificial light exposure and presented spherical form with aggregates, mean diameter of 177.9 ± 1.3 nm, 288.8 ± 1.4 nm, polydispersity index of 0.416, 0.496, and zeta potential -35.7, -30.5 mV, respectively. AgNPs obtained from dichloromethane extract incremented in the biological activities, with IC50 of 1.56 µg/mL and 0.25 µg/mL against K. pneumoniae and S. aureus, respectively, and IC50 of 0.28 µg/mL for A549 and 0.18 µg/mL for H292 cell lines. The development of AgNPs with dichloromethane extract of E. umbellata using green synthesis demonstrated high potential to be used as cytotoxic and antimicrobial product, associating the phytochemical composition and the presence of AgNPs in a synergic effect.